Predictive Value of Platelet-to-Lymphocyte Ratio and Neutrophil-to-Lymphocyte Ratio in Patients with Hypersensitivity Pneumonia: Platelet-To-Lymphocyte Ratio And Neutrophil-To-Lymphocyte Ratio In Hypersensitivity Pneumonia - Demirci Üçsular, Fatma; Polat, Gulru; Karadeniz, Gülistan; Ayrancı, Aysu; Keskin, Merve; Büyükşirin, Melih; Güldaval, Filiz; Yalnız, Enver (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Aim: To evaluate Platelet-to-Lymphocyte Ratio (PLR)   and Neutrophil-to-Lymphocyte Ratio (NLR)  in patients with HP.Method: A sample of 140 total patients, 50 having chronic HP and 20 having acute HP, and a  control group of 70 more patients were included in this retrospective study conducted with hospital  Ethical Committee approval.Results: PLR and NLR values ​​were significantly higher in all HP patients than in the control group ( p